Recurrent dermatofibrosarcoma protuberans of the breast: A case report and review of literature (Indian Journal of Case Reports, 2024)
Dermatofibrosarcoma protuberans (DFSP) is a rare and low-grade sarcoma of fibroblast origin with a tendency to invade and recur locally. The most common sites of origin of DFSP are the head, neck, and extremities. However, DFSP breast has also been reported. It infiltrates surrounding subcutaneous tissue and fascia, with an incidence of <2% for lung metastases. Surgery being the main modality of the treatment, literature has shown that radiation therapy also plays an important role to improve local control in case of recurrent tumors. In this article, we will be discussing one such rare case of DFSP in a recurrent setting and the role of radiation therapy.